1997
DOI: 10.1002/(sici)1097-0215(19970904)72:5<720::aid-ijc3>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pregnancy on the outcome of breast cancer: A case-control study

Abstract: The relationship between pregnancy and the outcome of breast cancer remains controversial. The purpose of this study was to determine the prognostic value of pregnancy at the time of diagnosis of primary infiltrating breast cancer. In a retrospective multi-center study we compared a group of 154 patients presenting pregnancy-associated (PA) breast cancer with a control group of 308 patients presenting non-pregnancy-associated (non-PA) breast cancer. Classic prognostic factors , treatment modalities, disease-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(65 citation statements)
references
References 24 publications
(21 reference statements)
5
55
1
4
Order By: Relevance
“…3 Of the premenopausal breast cancers diagnosed, approximately 58% are both estrogen receptor (ER) and progesterone receptor (PR) positive, 6% are ER positive only, 17% are PR positive only, and 20% are both ER and PR negative. 4 The management and treatment of breast cancer in premenopausal women can affect menstruation, reproduction, and gynecologic health. Breast cancer treatment can have a marked affect on fertility in women who have delayed childbearing and have fewer remaining reproductive years.…”
mentioning
confidence: 99%
“…3 Of the premenopausal breast cancers diagnosed, approximately 58% are both estrogen receptor (ER) and progesterone receptor (PR) positive, 6% are ER positive only, 17% are PR positive only, and 20% are both ER and PR negative. 4 The management and treatment of breast cancer in premenopausal women can affect menstruation, reproduction, and gynecologic health. Breast cancer treatment can have a marked affect on fertility in women who have delayed childbearing and have fewer remaining reproductive years.…”
mentioning
confidence: 99%
“…Several theories persist. The first is that the high circulating levels of estrogen and progesterone in pregnancy may occupy all of the hormone receptor binding sites; the second relates to receptor down-regulation during pregnancy [7,9,27,28].…”
Section: Pathologymentioning
confidence: 99%
“…Additionally, a retrospective and multi-institutional study from Bonnier and colleagues [27] found immunohistochemical assessment of hormone receptor status to be more reliable than a ligand-based assay. Ligand-based assays depend upon the availability of unbound hormone receptors, which may be less accurate during pregnancy secondary to interference by circulating steroid receptors.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of PABC is more often reported as being unfavorable [1,[7][8][9][10]. Whether this poor prognosis is related to pregnancy or mainly due to the young age of patientswhich in itself is known to be a poor prognostic factor [11] -is not clear.…”
Section: Introductionmentioning
confidence: 99%